1981
DOI: 10.1017/s0022029900021440
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic significance of milk glucose

Abstract: SummaryThe free glucose concentration in the aqueous phase of samples of goat, sheep, cow, rat and rabbit milk was about 0·1–0·3 mn, while that in human milk was about 2 mM. During starvation the glucose concentration of goat milk fell considerably (by about 80 % in 2 d) in parallel with the decreased rate of lactose production. With rats fed ad lib., glucose concentration in the milk was greater at 12.00 h than at 18.00 h, when lactose synthesis has been shown to decrease. 3-O-Methyl-D-glucose injected into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
45
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 17 publications
10
45
1
Order By: Relevance
“…The interrelationship between the three sugars, that is, the ratios thereby reflect energy metabolism in the cell, which, in turn, indicates the energy status of the animal, that is, in blood. In support of this, Faulkner et al (1981) demonstrated that starvation of goats for 2 days decreased glucose concentration of milk considerably in parallel with a decreased rate of lactose production. Chaiyabutr et al (1981) further demonstrated significantly reduced glucose uptake in the lactating mammary gland and increased concentration of G6P and other intermediate hexose-phosphates in milk during starvation of goats.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The interrelationship between the three sugars, that is, the ratios thereby reflect energy metabolism in the cell, which, in turn, indicates the energy status of the animal, that is, in blood. In support of this, Faulkner et al (1981) demonstrated that starvation of goats for 2 days decreased glucose concentration of milk considerably in parallel with a decreased rate of lactose production. Chaiyabutr et al (1981) further demonstrated significantly reduced glucose uptake in the lactating mammary gland and increased concentration of G6P and other intermediate hexose-phosphates in milk during starvation of goats.…”
Section: Discussionmentioning
confidence: 73%
“…This view is supported by most authors (e.g. Faulkner et al, 1981;Mepham, 1993). Two lines of evidence support this theory, that is, the equivalence of concentrations of glucose in isolated mammary cells and in milk, and the rapid equilibration of glucose across the apical cell membrane in experiments performed in vivo (see Faulkner and Peaker, 1987).…”
Section: Introductionmentioning
confidence: 75%
“…Blood glucose levels are tightly regulated in all mammals. The intracellular glucose concentrations are within 0.1-0.5 mM in mammary epithelial cells in most species where this was evaluated (72), a much lower range compared with plasma glucose levels. These data also indicate that lactose synthase is not saturated by glucose.…”
Section: Regulation Of Glucose Transporters and Their Role In Lactosementioning
confidence: 86%
“…In fact, glucose uptake in mammary gland is a key step in milk synthesis. Glucose is predominantly transported across MEC plasma membrane by facilitative or passive diffusion (4). This facilitative glucose transport in lactating bovine, human, and rat mammary glands predominantly takes place through GLUT1, an insulin independent glucose transporter (5-7).…”
Section: Expression Profiling Of Glucose Transporter 1 (Glut1) and Apmentioning
confidence: 99%